Constructing a course quality evaluation system based on hierarchical analysis and its application - Fu, Baojie (Frontiers in Education, 2026)
The fundamental issue in curriculum quality evaluation systems lies in how to scientifically and effectively measure the alignment between educational processes and student development objectives. Curriculum quality evaluation assesses whether teaching objectives are being achieved. Designing a rational and effective evaluation indicator system helps improve teaching quality, optimize curriculum reform, enhance student competence, and ensure curriculum quality. This study addressed the current research gap in higher education, where course quality evaluations rely heavily on subjective experience and lack a systematic quantitative analytical framework. It aimed to construct a quantifiable, multidimensional, and integrated comprehensive evaluation system for course quality to enhance the objectivity and scientific rigor of assessments. Using the core mining engineering course “Coal Mining” as an empirical case, it examined four key dimensions—faculty resources, teaching process, teaching resources, and teaching effectiveness—to systematically establish an evaluation indicator system for course quality. Methodologically, the study employed the analytic hierarchy process (AHP) to scientifically determine the weights of each evaluation indicator, thereby analyzing the impact of different dimensions on course quality. Subsequently, the fuzzy comprehensive evaluation method was applied to convert qualitative descriptions in the evaluation into quantitative analysis, addressing the inherent fuzziness and uncertainty in teaching evaluations. The results demonstrated that this approach not only achieves both qualitative judgments and quantitative scoring for course quality, effectively overcoming limitations of traditional evaluation methods, but also produces evaluation processes and outcomes characterized by higher reliability, rationality, and objectivity. The significance of this study lies in its provision of an empirical analytical model that combines theoretical grounding with practical applicability for quality diagnosis and continuous improvement in engineering education programs. The specific improvement measures proposed offer a direct reference for advancing curriculum reform and ensuring the quality of talent cultivation.